Provider payments and patient charges as policy tools for cost-containment: How successful are they in high-income countries? - Hanvoravongchai Piya; Carrin Guy (Human Resources for Health, 2003)
Abstract In this paper, we focus on those policy instruments with monetary incentives that are used to contain public health expenditure in high-income countries. First, a schematic view of the main cost-containment methods and the variables in the health system they intend to influence is presented. Two types of instruments to control the level and growth of public health expenditure are considered: (i) provider payment methods that influence the price and quantity of health care, and (ii) cost-containment measures that influence the behaviour of patients. Belonging to the first type of instruments, we have: fee-for-service, per diem payment, case payment, capitation, salaries and budgets. The second type of instruments consists of patient charges and reference price systems for pharmaceuticals. Secondly, we provide an overview of experience in high-income countries that use or have used these particular instruments. Finally, the paper assesses the overall potential of these instruments in cost-containment policies.